EFFORTS TO IMPROVE LEARNING MOTIVATION USING COOPERATIVE LEARNING MODEL TYPE STAD (STUDENT TEAM-ACHIEVEMENT DIVISION) STUDENTS GRADE VIII JUNIOR HIGH SCHOOL - Muhammad Fahrul Styawan; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The model of learning mathematic who are not appealing will make the student low in learning mathematic. This research aims to increase the motivation of learning mathematics by using a learning cooperative model type STAD student in class VIII A SMP Muhammadiyah Pakem Sleman District Academic Year 2016-2017. This study is a Classroom Action Research with the subject of research class VIII A SMP Muhammadiyah Pakem. Objects in this study are the motivation to learn mathematics students after learning mathematics with the STAD type cooperative learning model. The study was conducted in two cycles, each cycle consisting of two face-to-face. Data collection techniques used observation, interviews, and questionnaires to analyze data using qualitative and quantitative descriptive analysis. The results showed that the STAD type cooperative learning model could improve the motivation of learning mathematics students of class VIII A SMP Muhammadiyah Pakem Sleman District even semester of the academic year 2016/2017. This is evident from the observation of each cycle in the first cycle of 63.400% (Good), and the second cycle increased to 84.572% (Very Good). The result of the questionnaire of student's learning motivation shows that there is an increase of motivation to learn math that is seen from the mean of the survey of student's learning motivation in cycle I get percentage 70,789% (Good) and in period II increase to 82,616% (Very Good)—similarly, the results of interviews with teachers in the field of mathematics studies. From an interview with seven students of class VIII A can be concluded most of the students at the beginning of the meeting that is on the first cycle of a student, motivation has not been seen, because students have not understood the explanation submitted by researchers using STAD type cooperative learning model but at the next meeting and on cycle II Student motivation indicates an increase.